Incidence and risk factors for moderate and severe bronchopulmonary dysplasia in very low birth weight infants in two Croatian perinatal regions - a retrospective cohort study - Darjan Kardum; Boris Filipović-Grčić; Andrijana Müller; Sandro Dessardo (Hygeia Press di Corridori Marinella, 2019)
Introduction: Bronchopulmonary dysplasia (BPD) is a significant cause of mortality and morbidity in preterm infants. The incidence of BPD varies widely between centers and is found in 20% to 40% of very low birth weight (VLBW) infants. Our work aimed to examine the incidence and risk factors for moderate and severe BPD in a population of VLBW infants. Materials and methods: Demographic data, risk factors, incidence and severity of BPD were analyzed for 178 VLBW infants treated in two Croatian perinatal regions (2 level III neonatal units, 2 level II neonatal units and 5 level I neonatal wards) in the period from January 1, 2014 to December 31, 2016. Results: The rate of BPD was 59.6% (106/178) which is significantly higher than reported earlier. Mild BPD accounted for 65.1% (69/106) and moderate/severe BPD is found in 34.9% (37/106) infants. Among infants with ≤ 28 weeks of gestation, the rate of moderate and severe BPD was 40.5% (30/74). Ultimate risk factors for the development of moderate/severe BPD were late-onset sepsis (p = 0.03; OR [95% CI]: 4.76 [1.22-18.5]), and higher initial neonatal risk as expressed by Critical Risk Index for Babies (CRIB) score (p < 0.001; OR [95% CI]: 1.73 [1.32-2.29]). Conclusion: The incidence of moderate and severe BPD in our study group is higher than previously reported, and the majority of affected infants are < 29 weeks of gestation. The factors that had the strongest influence on the development of moderate and severe BPD were a higher initial neonatal risk as expressed by CRIB score and late-onset sepsis.